Exploration of passive desaturation of in place tailings using wicking geosynthetics - Monley, Kendall O., author; Scalia, Joseph, IV, advisor; Bareither, Christopher, committee member; Ross, Matthew, committee member (Colorado State University. Libraries, 2024)
As global demand for metals and critical minerals increases, so too does the production of tailings. Tailings are what is left behind after extraction of valuable metals and minerals from ore, and consist of finely ground rock, water, unrecoverable metals, chemicals, and organic matter. These residuals are managed in engineered facilities that function to both dewater and store tailings, known as tailings storage facilities (TSF). A common assumption is that the water initially contained in TSFs will drain down to an unsaturated condition after deposition of new tailings ceases. However, a review of literature on geotechnical and hydrotechnical conditions of legacy TSFs (TSFs that have stopped receiving tailings) in arid environments illustrates that achievement of unsaturated conditions in internal fine-grained layers may not always occur. As the tailings are deposited, layers of finer and coarser particles are interbedded. This causes the formation of capillary barriers and may ultimately result in finer-grained layers held at near saturation after drain down. These fine-grained layers are more susceptible to liquefaction concerns and can require costly remedial actions to ensure geotechnical stability. Dewatering is the process of removing water from whole tailings and offers benefits including increasing geotechnical stability and recovering stored water. Tailings dewatering may occur prior to or after deposition into a TSF. In this study, I explore in-situ dewatering via use of capillary (wicking) geotextiles, and the effectiveness of the wicking geotextiles. Beaker and column experiments were created to emulate stratigraphy seen in legacy TSFs. Additionally, shrinkage testing was conducted to compare the final densities and void ratios of samples with and without wicking geotextiles. Column testing reveals the wicking geotextiles accelerated dewatering by 2.8 times the rate of natural drying processes. At the conclusion of testing, the wicking geotextile experiments had reached similar densities and void ratios to control experiments. This novel approach to passively dewatering tailings warrants additional testing.
Keywords: geosynthetics; mining; capillary barriers; tailings; geotechnical